'The Most Amazing Show': performative interactions with postelection South African society and culture - Scholtz, Brink (Rhodes University, Faculty of Humanities, Department of Drama, 2008)
This research investigates contemporary South African performance within the context of prominent social and cultural change following the political transition from an apartheid state to democracy. Specifically, it looks at the relationship between a popular comic variety show The Most Amazing Show (TMAS), and aspects of contemporary South African society and culture, particularly relating to prominent efforts to affect post-election transformation of South African society and culture through the construction of a South African 'rainbow nation'. By analysing TMAS in terms of broader historical, performative and discursive contexts, it engages a relational reading of the performance. The study argues that TMAS both challenges and participates in the manner in which rainbow nation discourse constructs South African society and culture. Firstly, it considers the performance's construction of hybrid South African identities, including white Afrikaans, white English and white masculine identities. It argues that these reconstructions undermine the tendency within rainbow nation discourse to construct cultural hybridity in terms of stereotypically distinct identities. Secondly, it considers TMAS' construction of collective experience and social integration, which subverts the often glamorised and superficial representations of social healing and integration that are constructed within rainbow nation discourse. The analysis makes prominent reference to the notion of 'liminality' in order to describe the manner in which TMAS constructs significance within the tension that it establishes between oppositional, and often contradictory, positions. Furthermore, it attempts to establish a link between this notion of liminality and notions of theatrical syncretism that are prominent in contemporary South African theatre scholarship, and emphasise processes of signification that are constantly shifting and unstable.
Keywords: Performing arts; Drama -- Study and teaching; Recreational activities